Event sustainability practices among professional company organizers: an exploratory study - Zamzuri, Norol Hamiza; Awang, Khairil Wahidin; Abdul Aziz, Yuhanis; Samdin, Zaiton (Penerbit Universiti Teknologi Malaysia, 2013)
The growth of business event results in a potential impact to the environment if the waste from event materials is not properly managed by event organizers. The waste from event materials can create negative impact to the environment. This problem leads to the emergence of several sustainable strategies practiced by stakeholders, however, little is known on the issues involve in the process of organizing a sustainable event. Therefore, the aim of this study is to explore the issues involved during the process of organizing a sustainable event. Inductive method was used in this study as it gives better insight on the real phenomenon. The data were collected from event organizers through in-depth interviews.